RI 3033 The Action of Sulphur Dioxide on Manganese Oxides at Elevated Temperatures (812e3a3a-4fa4-451e-b693-5c77977e70f5) - C. W. Davie (The National Institute for Occupational Safety and Health (NIOSH), 1930)
"This paper is the second of a series of progress reports4 on a study of the hydrometallurgy of manganese which is being conducted in an endeavor to make possible utilization of the large deposits of low-grade domestic manganese ores that occur in several States.There are at least four processes in which a knowledge of the action of SO2 gas on manganese oxides at elevated temperatures may prove of value.One of these involves dissolution of manganese from ores. The Bureau of Mines has investigated the hydrometallurgy of manganese by a process in which SO2 gas, a waste product at many smelters, is passed into water to form a solvent for manganese. Although several manganese minerals were readily dissolved, rhodochrosite (MnCO3) was attacked but superficially.5 Recent experiments have shown that a roast at 650 to 9000 C. converts the manganese of rhodochrosite to a form that is quickly dissolved by a weak SO2 solution.6 Introduction of smelter gases containing much as 5 per cent SO2 during such a roast would not add much to the cost of the operation, and might result in the formation of considerable water-soluble manganese sulpate.Another case involves a subsequent step in the hydrometallurgical process, namely, the formation of oxides of manganese with simultaneous evolution of SO2 by the heating of the MnSO4 produced by evaporating its solution.A third has to do with the roasting of zinc sulphide ores containing manganese as a preliminary to leaching. During purification of the solutions to be used for the electrolytic deposition of zinc the iron must be oxidized to make possible its removal. Manganese dioxide has been used for this purpose,7 and since manganese compounds are present in some zinc concentrates,8 it is of interest to learn what happens to the manganese in a zinc sulphide or on roasting, and what portion of the manganese in the roasted product might be available for oxidation."